PREVENTION OF CARIES OF PERMANENT TEETH IN PRIMARY SCHOOL CHILDREN - Kurbonova Mahliyo Tavakalovna (Journals Park Publishing, 2022)
The paper discusses etiologic factors of caries disease directly and indirectly connected with the development of the disease process. The authors point to the relationship between the occurrence of early childhood caries and colonization time of oral cavity by cariogenic germs and present the relationship between caries in deciduous and permanent teeth.
Keywords: early childhood; colonization; early prophylactic activity